Correlations of total phenolics and antioxidant activity in royal jelly from Bosnia and Herzegovina - Toromanović, Jasmin; Medunjanin, Damir; Dizdar, Muamer; Buza, Nermin; Trešnjo, Adis; Tahirović, Ismet (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2024)
In this study, the total phenolics content (TPC), and antioxidant activity against hydroxyl (AAOH·) and peroxyl (AAROO·) free radicals in centrifuged (low molecular weight fractions, LM) and uncentrifuged (the bulk of low molecular weight and high molecular weight, LM+HM fractions) samples of fresh royal jelly (RJ) from Bosnia and Herzegovina (B&H), as well as correlations between these parameters were determined. For determination of the TPC, spectrophotometric method with gallic acid (GA) as the standard was used. For the determination of AA, the oxygen radical absorbance capacity (ORAC) assay with catechin as the standard was used. The highest TPC expressed in equivalent mass of GA per mass of RJ (LM+HM fractions) was found in the sample from Kalinovik, 5.54±0.76 mg GAE/g, and in the sample from Bosanska Krupa, 4.07±0.04 mg GAE/g for LM phenolics of RJ. The highest AAOH·expressed as mmol catechin equivalents (CE) per mass of LM+HM fraction of RJ was found in the sample from Cazin 58.15±1.55 mM CE/g, and in the sample from Ključ, 58.15±0.81 mM CE/g for LM fraction. The highest AAROO· per mass of LM+HM fraction of RJ was found in the sample from Bosanska Krupa, 8.04±0.04 mM CE/g, in which also found the highest AAROO·for LM fractions, 7.58±0.39 mM CE/g. There were very high positive correlations between AAOH·(LM+HM), as well as AAOH·(LM)) and TPC(LM+HM), as well as TPC(LM) (Pearson correlations (P.c.)). It was moderate positive correlation AAOH·(HM)to TPC(HM). Also, there were weak positive correlations between AA(ROO·)(LM+HM), as well as AA(ROO·)LM and TPC(LM+HM), as well asTPC(LM), and weak negative correlation AA(ROO·)(HM) to TPC(HM). Based on a very high TPC and significant AA, it can be concluded that RJ from B&H is a good source of natural antioxidants and is an important dietary supplement.